“That Says, For Me, You Are a Second-Class Citizen”: A Concept Analysis of Accessibility - Gareth Terry; David Anstiss; Joanna Fadyl; Deborah Payne; Rachel Allan; Nicola Kayes (International Journal of Disability and Social Justice)
Accessibility is useful to consider conceptually to contribute to the discussion about why its societal benefits are under-recognised. We sought to propose a conceptualisation of accessibility that draws together prior scholarly work on accessibility as it relates to disability from across disciplines and knowledge of stakeholders with lived experience of disability. Data sources included a literature review, focus group and interview discussions, and consultation with local disability advocacy and support organisations. We used a concept analysis, identifying different ways in which the notion of accessibility was deployed across our data. The resulting conceptual framework positions accessibility as the enablement of a full range of life’s experiences to be understood, reached, and experienced equally and fully by everyone. Highly relevant but often overlooked in scholarly literature on geography and rehabilitation is the idea that to create accessible experiences the ongoing actions of each person matter: from policy to design to everyday encounters.